2016
DOI: 10.1111/jopr.12481
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of the Accuracy of Dies Made from Digital Intraoral Scanning vs. Elastic Impressions: An In Vitro Study

Abstract: PVS/Die and iTero groups offered superior reproduction of the master die in terms of dimensional accuracy, but these differences are likely of little clinical significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 21 publications
(45 reference statements)
0
14
0
3
Order By: Relevance
“…Yet, recent studies confirm that models obtained from a digital intra-oral scanning have a dimensional accuracy equivalent to that of plaster stone casts models obtained after traditional impressions (M. Serag et al, 2018) [12] and that intraoral scanners have an equally or higher accuracy and precision than conventional impressions, and these can be used when restoring up to ten units, without extended edentulous spans (R. Nedelcu et al, 2018) [13].…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Yet, recent studies confirm that models obtained from a digital intra-oral scanning have a dimensional accuracy equivalent to that of plaster stone casts models obtained after traditional impressions (M. Serag et al, 2018) [12] and that intraoral scanners have an equally or higher accuracy and precision than conventional impressions, and these can be used when restoring up to ten units, without extended edentulous spans (R. Nedelcu et al, 2018) [13].…”
Section: Resultsmentioning
confidence: 90%
“…On the other hand, most of the recent studies conclude that intraoral scanning provides higher precision and trueness when compared to the conventional impression or to extraoral scanning [12,13,22,23]. It was also shown that the new generations of printers produce clinically acceptable models that represent a good, viable option for clinical applications [24,25].…”
Section: Resultsmentioning
confidence: 99%
“…Ender et al (2019) [19], specifies that: "certain current IOS devices are well within the required accuracy required for full-arch scansˮ and -corresponding to partial-arch impressions -"IO scanninig represents a suitable alternative to conventional impression methodsˮ. The intraoral scanning is described by many authors as being able to provide greater accuracy of dental models, compared to the laboratory (extraoral) scanning or to the conventional method of obtaining dental models, represented by conventional oral impression [20,21,22,14]. Sason et al (2018) [20] presented an in vivo study performed on 10 clinically healthy patients, aged 18-45, highlighting that the intraoral scanner offers greater accuracy (precision and trueness) than the extraoral scanner.…”
Section: Resultsmentioning
confidence: 99%
“…Deste modo, as chances de alterações interproximais causadas pela serra do troquel diminuem 5,14 . Várias etapas laboratoriais podem ser eliminadas, como: o vazamento do gesso nas moldagens, a confecção das réplicas, a colocação dos pinos nos modelos além de não necessitar recortar e modelar troqueis 2,15,16 . O registro oclusal também é realizado durante o escaneamento, e os modelos são impressos com guia de articulação 16,17 .…”
Section: Ciência Pluralunclassified
“…Alguns estudos já evidenciam que o escaneamento intra oral apresenta boa capacidade de cópia dos preparos 5,6,12,16,17,18 . Sendo o objetivo do presente artigo, relatar em um caso clínico a confecção de nove laminados cerâmicos em que foi empregado escaneamento intra oral e confecção dos modelos em impressora 3D.…”
Section: Ciência Pluralunclassified